How to Prevent or Reduce Prescribing Errors: An Evidence Brief for Policy - de Araújo, Bruna Carolina; de Melo, Roberta Crevelário; de Bortoli, Maritsa Carla; Bonfim, José Ruben de Alcântara; Toma, Tereza Setsuko (Frontiers in Pharmacology, 2019)
- Preventing prescribing errors is critical to improving patient safety. - We developed an evidence brief for policy to identify effective interventions to avoid or reduce prescribing errors. - Four options were raised: promoting educational actions on prudent prescribing directed to prescribers; incorporating computerized alert systems into clinical practice; implementing the use of tools for guiding medication prescribing; and, encouraging patient care by a multidisciplinary team, with the participation of a pharmacist. - These options can be incorporated into health systems either alone or together, and for that, it is necessary that the context be considered. - Aiming to inform decision makers, we included considerations on the implementation of these options regarding upper-middle income countries, like the Brazilian, and we also present considerations regarding equity.